Targeting NK Cell Inhibitory Receptors for Precision Multiple Myeloma Immunotherapy - Alfarra, Helmi; Weir, Jackson; Grieve, Stacy; Reiman, Tony (Frontiers in Immunology, 2020)
Innate immune surveillance of cancer involves multiple types of immune cells including the innate lymphoid cells (ILCs). Natural killer (NK) cells are considered the most active ILC subset for tumor elimination because of their ability to target infected and malignant cells without prior sensitization. NK cells are equipped with an array of activating and inhibitory receptors (IRs); hence NK cell activity is controlled by balanced signals between the activating and IRs. Multiple myeloma (MM) is a hematological malignancy that is known for its altered immune landscape. Despite improvements in therapeutic options for MM, this disease remains incurable. An emerging trend to improve clinical outcomes in MM involves harnessing the inherent ability of NK cells to kill malignant cells by recruiting NK cells and enhancing their cytotoxicity toward the malignant MM cells. Following the clinical success of blocking T cell IRs in multiple cancers, targeting NK cell IRs is drawing increasing attention. Relevant NK cell IRs that are attractive candidates for checkpoint blockades include KIRs, NKG2A, LAG-3, TIGIT, PD-1, and TIM-3 receptors. Investigating these NK cell IRs as pathogenic agents and therapeutic targets could lead to promising applications in MM therapy. This review describes the critical role of enhancing NK cell activity in MM and discusses the potential of blocking NK cell IRs as a future MM therapy.